The High Light Response in Arabidopsis Requires the Calcium Sensor Protein CAS, a Target of STN7- and STN8-Mediated Phosphorylation - Cutolo, Edoardo; Parvin, Nargis; Ruge, Henning; Pirayesh, Niloufar; Roustan, Valentin; Weckwerth, Wolfram; Teige, Markus; Grieco, Michele; Larosa, Veronique; Vothknecht, Ute C. (Frontiers in Plant Science, 2019)
Reversible phosphorylation of thylakoid proteins contributes to photoacclimation responses in photosynthetic organisms, enabling the fine-tuning of light harvesting under changing light conditions and promoting the onset of photoprotective processes. However, the precise functional role of many of the described phosphorylation events on thylakoid proteins remains elusive. The calcium sensor receptor protein (CAS) has previously been indicated as one of the targets of the state transition kinase 8 (STN8). Here we show that in Arabidopsis thaliana, CAS is also phosphorylated by the state transition kinase 7 (STN7), as well as by another, so-far unknown, Ca2+-dependent kinase. Phosphoproteomics analysis and in vitro phosphorylation assays on CAS variants identified the phylogenetically conserved residues Thr-376, Ser-378 and Thr-380 as the major phosphorylation sites of the STN kinases. Spectroscopic analyses of chlorophyll fluorescence emission at 77K further showed that, while the cas mutant is not affected in state transition, it displays a persistent strong excitation of PSI under high light exposure similar to the phenotype observed for mutants of thylakoid-associated phosphatase 38 (tap38/pph1) and proton gradient regulation 5 (pgr5). Together with the observation of a strong concomitant phosphorylation of light harvesting complex II (LHCII) and photosynthetic core proteins under high irradiance in the cas mutant this suggests a role for CAS in the STN7/STN8/TAP38 network of phosphorylation-mediated photoacclimation processes in Arabidopsis.